Functional Nutritional and Sensory Properties of Seasoning Powders from Fermented African Locust Bean Chicken and Shiitake Mushrooms - (:unkn) unknown (My University, 2025)
Seasoning powders can be deﬁned as mixtures of different compounds whose main role is to enhance taste and ﬂavor of ready to eat food to which they are added. The taste enhancement property of the seasoning powders is largely due to the presence of flavour enhancers in them which elicit the umami or savoury taste when added to food. Generally commercial powdered seasonings are made from monosodium glutamate (MSG), a potent flavour enhancer which has been accused of being responsible for many health problems such as brain damage. The aim of this study was to formulate of blends of seasoning powders from African locust bean seeds, chicken and mushroom and assessment of their functional, nutritional and taste properties. The development of functional seasonings is necessary as the commercial seasonings available in the market are full of the controversial MSG and deemed unfit for consumption. Four combinations were made containing different proportions of iru, chicken and mushroom (I/C/M) as follows 1 (16.6/16.6/66.7), 2(16.6/66.7/16.6), 3(66.7/16.6/16.6), 4(33.3/33.3/33.3). The functional, nutritional and sensory properties of the seasoning powders were evaluated using standard analytical procedures (AOAC 2020). There was no significant difference at P>0.05 in the bulk densities of all the four blends. The blend containing 66.7% chicken powder had the highest protein content 50.32±1.18%.all the seasoning powder blends had less than 1% monosodium glutamate while free glutamic acid was found to most abundant 443.39 ± 1.44mg/100g in the blend containing more iru: 3(66.7/16.6/16.6) (I/C/M). This same blend was considered to be the most acceptable product as it had the highest general acceptability score 8.22 ± 0.17.the high protein content of this seasoning powder is advantageous as it makes it not only a flavour enhancer but also a nutrient-dense food product. The ingredients for this seasoning powders: African locust bean, chicken, mushrooms
Keywords: African Research